Kincir Angin Crossflow 8 sudu dengan Variasi Pitch Angle - YB Lukiyanto (ReTII, 2024)
Wind energy is one of variant of renewable energy resources of Indonesia. Wind mills was one of equipments to convert wind energy to shaft mechanical work. A type of vertical axis windmill whose characteristics was not widely known was cross flow windmill. The purpose of this research was to investigate a cross flow windmill with eight blades, 78 cm diameter and 90 cm height. The variation on the research was adjust the pitch angle of the blade, to be 0, 10 and 20 degrees, respectively. Based on the observations that have been made was obtained a graph of the relationship between Cp and tsr of the windmill. Based on the graph, the cross flow windmill with pitch angle of 20 degree gives the largest Cp value, about 4.3 percent with the largest tsr value range, between 0.14 and 0.49. The graph of Cp and tsr relationship for a cross flow windmill with pitch angle of blades 20 degree was below the Cp and tsr relationship of American Wind Mill windmills. Keyword : windmill, cross flow, eight blades, pitch angle